2017
DOI: 10.1017/s1041610217001740
|View full text |Cite
|
Sign up to set email alerts
|

Conversational assessment of cognitive dysfunction among residents living in long-term care facilities

Abstract: Background:There are some existing barriers posed by neuropsychological tests that interfere with the assessment of cognitive functioning by staff who work in long-term care facilities. The purpose of this study was to investigate the feasibility of assessing cognitive function through conversation.Methods:A total of 100 care staff was randomly selected as participants. Each staff member evaluated cognitive function in one to three residents using the Conversational Assessment of Neurocognitive Dysfunction (CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 24 publications
0
15
1
Order By: Relevance
“…A dementia specialist (K.P.) interviewed all participants with their families, examined the participants, and ruled out dementia based on MRI findings and neuropsychological tests including the Conversational Assessment of Neurocognitive Dysfunction, newly developed for dementia diagnosis based on daily conversations 25 . We collected the medical histories of participants and confirmed that none had cerebrovascular disorders, brain tumours, or cardiovascular disease.…”
Section: Methodsmentioning
confidence: 99%
“…A dementia specialist (K.P.) interviewed all participants with their families, examined the participants, and ruled out dementia based on MRI findings and neuropsychological tests including the Conversational Assessment of Neurocognitive Dysfunction, newly developed for dementia diagnosis based on daily conversations 25 . We collected the medical histories of participants and confirmed that none had cerebrovascular disorders, brain tumours, or cardiovascular disease.…”
Section: Methodsmentioning
confidence: 99%
“…A dementia specialist (K.P.) interviewed all participants with their families, examined the participants, and ruled out dementia based on MRI ndings and neuropsychological tests including the Conversational Assessment of Neurocognitive Dysfunction (CANDy) newly developed by us for dementia diagnosis based on daily conversations [25] . None of the participants had cerebrovascular disorders or brain tumours.…”
Section: Participantsmentioning
confidence: 99%
“…Finally, the participant’s fingertip volume pulse wave was recorded in an autonomic test. A staff member who frequently spoke with the participants in the facility was asked to respond to the Conversational Assessment of Neurocognitive Dysfunction (CANDy) [ 43 ] to assess the participants’ daily conversation skills. Thereafter, the intervention with the participants by providing the designated brown or white rice was commenced.…”
Section: Protocolmentioning
confidence: 99%
“…CANDy [ 43 ] is a 15-question scale based on which others rate the characteristics of the daily conversation of the elderly with dementia. This scale has a maximum score of 30 points, with high scores indicating the presence of a variety of conversational features.…”
Section: Measurement Itemsmentioning
confidence: 99%